2016
DOI: 10.1111/mec.13806
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microbial populations driving biopolymer degradation in acidic peatlands by metatranscriptomic analysis

Abstract: Northern peatlands play a crucial role in the global carbon balance, serving as a persistent sink for atmospheric CO2 and a global carbon store. Their most extensive type, Sphagnum-dominated acidic peatlands, is inhabited by microorganisms with poorly understood degradation capabilities. Here, we applied a combination of barcoded pyrosequencing of SSU rRNA genes and Illumina RNA-Seq of total RNA (metatranscriptomics) to identify microbial populations and enzymes involved in degrading the major components of Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 82 publications
3
42
0
1
Order By: Relevance
“…This study began with attempts to detect the substrate-induced response of F. ruber-like planctomycetes to amendment of Sphagnum-derived peat from the peat bog Obukhovskoye with chitin. For this purpose, we reanalyzed the small subunit (SSU) rRNA data set retrieved in our recent metatranscriptomic study (19), which assessed the substrate-induced response of peat-inhabiting microorganisms to amendments with various key biopolymers, including cellulose, xylan, pectin, and chitin. The 16S rRNA reads from F. ruber-like planctomycetes were sorted out using a species-level identity threshold of 97% from the sequence sets corresponding to four experimental incubations with different biopolymers and the control incubation without added substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study began with attempts to detect the substrate-induced response of F. ruber-like planctomycetes to amendment of Sphagnum-derived peat from the peat bog Obukhovskoye with chitin. For this purpose, we reanalyzed the small subunit (SSU) rRNA data set retrieved in our recent metatranscriptomic study (19), which assessed the substrate-induced response of peat-inhabiting microorganisms to amendments with various key biopolymers, including cellulose, xylan, pectin, and chitin. The 16S rRNA reads from F. ruber-like planctomycetes were sorted out using a species-level identity threshold of 97% from the sequence sets corresponding to four experimental incubations with different biopolymers and the control incubation without added substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Recent molecular study of microbial degradation of chitin in an agricultural soil suggested involvement of Singulisphaera-like planctomycetes in this process (18). Additional evidence for the existence of chitinolytic planctomycetes was obtained in a metatranscriptome-based study of microbial populations driving biopolymer degradation in acidic peatlands (19). Although no changes in the relative abundance of planctomycetes within the whole bacterial community were observed in response to the amendment with chitin, some groups within uncultivated planctomycetes, in particular Gemmata-like bacteria, were clearly stimulated by the availability of this biopolymer.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…As revealed by molecular surveys, these bacteria are common inhabitants of boreal Sphagnum -dominated peatlands (Dedysh, 2011; Ivanova and Dedysh, 2012; Serkebaeva et al, 2013; Tveit et al, 2013; Moore et al, 2015; Ivanova et al, 2016). Although several peat-inhabiting planctomycetes have been obtained in pure cultures (Dedysh and Kulichevskaya, 2013), we know very little about their potential functions in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Sphagnum -dominated boreal wetlands represent one of the most extensive terrestrial low-temperature environments where members of the Planctomycetes are especially widespread and abundant (Dedysh et al, 2006; Kulichevskaya et al, 2006; Bragina et al, 2012, 2015; Ivanova and Dedysh, 2012; Serkebaeva et al, 2013; Moore et al, 2015; Ivanova et al, 2016). The predominant planctomycete populations in northern wetlands are represented by members of the phylogenetic group defined by the genera Isosphaera and Singulisphaera (Ivanova and Dedysh, 2012; Serkebaeva et al, 2013; Moore et al, 2015).…”
Section: Introductionmentioning
confidence: 99%